Predicting the results of uterine artery embolization: correlation between initial intramural fibroid volume and percentage volume decrease - Czuczwar, Piotr; Woźniak, Sławomir; Szkodziak, Piotr; Woźniakowska, Ewa; Paszkowski, Maciej; Wrona, Wojciech; Milart, Paweł; Paszkowski, Tomasz; Popajewski, Michał (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction and objective : Uterine artery embolization (UAE) is a minimally invasive treatment option for symptomatic fibroids. Long-term follow-up studies have shown that at five-year follow-up after UAE, up to 30% of patients required a hysterectomy. Therefore, it seems of utmost importance to identify patients, who are unlikely to benefit from UAE. It has been postulated that the percentage volume reduction of fibroids may predict long-term UAE outcome. The results of available studies are equivocal, therefore it seemed of interest to investigate the correlation between the preinterventional intramural fibroid volume and imaging outcome of UAE in premenopausal patients. Material and methods : Uterine artery embolization was performed in 65 premenopausal patients with symptomatic, intramural fibroids. Dominant fibroid volume was assessed using an integrated VOCAL (Virtual Organ Computer-aided AnaLysis) imaging program at baseline and 3 months after UAE. The percentage reduction of fibroid volume was calculated. The association between preinterventional fibroid volumes and percentage volume reductions was determined with the Spearman rank correlation test. Results : Before UAE, the median dominant fibroid volume was 101 cm3 (range 23.6-610). At three-month follow-up the median dominant leiomyoma volume decreased to 50.4 cm3 (range 6.9-193.9). Median percentage reduction of fibroid volume three months after UAE was calculated at 50.1% (range 2.7-93.5). The Spearman correlation test between the preinterventional dominant fibroid volume and percentage volume reduction showed a statistically significant, positive correlation (R = 0.33; p = 0.006). Conclusions : The percentage volume reduction of intramural leiomyomas after UAE seems to be more pronounced in the case of larger tumors.